PROFIT AND LOSS ACCOUNT AND THE PERFORMANCE OF AN ECONOMIC ENTITY IN ROMANIA - BOGDĂNOIU, Cristiana Luminița (Journal of Advanced Research in Management, 2020)
The article aims to present the results and accounting performance of an economic entity. Achieving this objective, it is required the identification of the information provided by the profit and loss account and, on this basis, the construction of a performance analysis scheme. This analysis scheme allows us, the overall analysis of the financial performances, at global level of the activity of an economic entity, but also analytical, for each type of activity, respectively exploitation and financial, the analysis of the evolution of their financial and structural performances.